Antibiotic Susceptibility of Clinical Isolates of Listeria monocytogenes - Wiggins, Geraldine L. (1978)
A broth microdilution method was used to measure the minimal inhibitory concentrations (MICs) of the antibiotics most often recommended for treatment of listeriosis. The MICs of ampicillin, penicillin, erythromycin, and tetracycline for 175 strains of Listeria monocytogenes were below the approximate MIC breakpoint for susceptible strains as recommended by the National Committee on Clinical Laboratory Standards. Inhibition diameters for 125 strains were measured by the standardized disk method (National Committee on Clinical Laboratory Standards) and compared with the appropriate MIC values. By both methods, strains were susceptible to the above four antibiotics, except for three strains, which were intermediate in susceptibility to penicillin by the disk method. Since the minimal bactericidal concentrations for ampicillin and penicillin significantly exceeded the MICs for these antibiotics, 45 strains were evaluated with ampicillin (5 μg/ml) and gentamicin (1 μg/ml) to compare the synergistic bactericidal effect of the two used in combination and singly. An increased kill of 100-fold was observed with the antibiotics combined in 19 strains after 4 to 6 h and in 40 strains after 24 h. A comparison of results with microdilution in Trypticase soy broth and agar dilution in Mueller-Hinton agar revealed that MICs for gentamicin, kanamycin, and streptomycin were strongly influenced by the media used. The MICs were consistently lower in Mueller-Hinton agar.